Adsorption and identification of traces of dyes in aqueous solutions using chemically modified eggshell membranes. (September 2019) - Candido, Iuri Custodio Montes; Soares, Juliana Mikaelly Dias; de Araujo Barros Barbosa, Jaderson; de Oliveira, Helinando Pequeno
Abstract: This paper describes the adsorption of methylene blue and methyl orange from aqueous solution by eggshell membrane (pristine/modified with silver nanoparticles) which were analyzed by Fourier Transform Infrared/Raman spectroscopy and Scanning Electron Microscopy. The conditions for adsorption were varied in terms of pH, adsorbent mass, dye concentration and time of reaction. The equilibrium condition was evaluated according Langmuir, Freundlich, Temkin and Dubinin-Radushkevich isotherms while the adsorption kinetics was fitted by PSO/PFO and Elovich models. The results indicated that Freundlich model and PSO were better fitted by comparison with other models. In addition, the incorporation of silver nanoparticles favors the detection of dyes traces using the Surface Enhance Raman Spectroscopy (SERS method) in concentration as low as 10 −9  M. The good desorption rate observed indicated that membrane has great potential for use as adsorbent and SERS support for dye traces detection. Highlights: Eggshell membrane-based devices were developed by modification of silver particles. The adsorption of acidic and basic dyes is favored on decorated eggshell membranes. The identification of contaminant traces is provided by hot spots on membranes. The SERS signal is favored by high concentration of silver nanoparticles on membrane.